1997
DOI: 10.1016/s0741-5214(97)70161-7
|View full text |Cite
|
Sign up to set email alerts
|

Floating thrombus in the ascending aorta: A rare cause of peripheral emboli

Abstract: The ascending aorta may be the site of origin of systemic embolization in some cases that do not have an identifiable source. We report a case in which a free-floating thrombus in the noncoronary sinus of Valsalva was detected by transesophageal echocardiography as a source of left axillary artery embolism. After removal of this pedunculated thrombus of unknown cause, which was attached on a macroscopically and histologically normal aortic wall, the patient made an uneventful recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 17 publications
(1 reference statement)
2
64
0
Order By: Relevance
“…Kalangos et al suggested that the role of a transient hypercoagulable state that is not well understood at the present time, in a site such as the aortic sinus of Valsalva where turbulence could act as a contributing factor, remains a reasonable possibility. 2 So, we speculate that the etiology of this case is the result of the combination of alcoholic dehydration and Af.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Kalangos et al suggested that the role of a transient hypercoagulable state that is not well understood at the present time, in a site such as the aortic sinus of Valsalva where turbulence could act as a contributing factor, remains a reasonable possibility. 2 So, we speculate that the etiology of this case is the result of the combination of alcoholic dehydration and Af.…”
Section: Discussionmentioning
confidence: 81%
“…If we fi nd a fl oating mass in the left-side heart or in the aorta, especially in the ascending aorta, we should start treatment to the mass immediately before major embolic complications occur. [1][2][3] We report a case of fl oating thrombus in the ascending aorta. Surgical removal of the thrombus was performed successfully.…”
Section: Introductionmentioning
confidence: 97%
“…What is unusual about this case is that the remainder of the aorta, mesenteric vessels and coronaries were all without any atherosclerosis. A pubmed search conducted using the terms (mobile thrombus) and (aorta) resulted in 102 publications, ten of which involved patients with mobile aortic thrombi without identified risk factors [3][4][5][6][7][8][9] (see Table 1). …”
Section: Discussionmentioning
confidence: 99%
“…Floating thrombi in the ascending aorta have a clinical presentation that includes acute or chronic recurrent cerebrovascular or peripheral embolic symptoms [5], which suggests an embolic path through the branches of the aortic arch or down the distal aorta. To our knowledge, this is the first case of ascending aortic thrombus with only emboli to the abdominal viscera.…”
Section: Discussionmentioning
confidence: 99%
“…Since the ideal treatment of mobile aortic thrombi without atheromatosis has not been ascertained, the immediate treatment is usually selected according to the underlying pathology and patients' comorbidities. It is also emphasized that surgery should always be considered in the absence of risk factors for surgery (e.g., atherosclerosis), especially if systemic embolism occurs (10,11).…”
mentioning
confidence: 99%